AMPGen: an evolutionary information-reserved and diffusion-driven generative model for de novo design of antimicrobial peptides - Shuwen Jin; Zihan Zeng; Xiyan Xiong; Baicheng Huang; Li Tang; Hongsheng Wang; Xiao Ma; Xiaochun Tang; Guoqing Shao; Xingxu Huang; Feng Lin (Communications Biology)
Abstract The rapid advancement of artificial intelligence (AI) has enabled de novo design of functional proteins, circumventing the reliance on natural templates or sequencing databases. However, current protein design models are ineffective in generating proteins without stable structures, such as antimicrobial peptides (AMPs), which are short and structurally flexible yet play critical biological roles. To address this challenge, we present AMPGen, an evolutionary information-reserved and diffusion-driven generative model for de novo design of target-specific AMPs. AMPGen innovates AI tools, including a generator, a discriminator, and a scorer, along with biochemical knowledge-based screening programs. The generator employs a pre-trained, order-agnostic autoregressive diffusion model, which performs axial attention to capture protein evolutionary information from multiple sequence alignments (MSAs). The AMP-MSA conditional input raises the success rate of generated AMPs, which are subsequently filtered based on physicochemical properties and assessed by an XGBoost-based discriminator. The final target-specific scoring is performed with an LSTM-based scorer, resulting in high-quality AMP candidates. In this study, of the 40 de novo designed AMP candidates for verification, 38 were successfully synthesized, and among them, 81.58% demonstrated antibacterial activity. These AMPs designed by AMPGen are absent from existing AMP databases, and exhibit high antibacterial capacity, sequence diversity, and broad-spectrum activity.